Aid, Policies and Growth: A Non-Canonical Alternative for solving This Puzzle. - Raúl Fuentes (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
This paper presents a two-sector small semi-open economy Ramsey growth model involving foreign aid as an input in the production function. An activist government allocates this input endogenously across sectors and optimizes policies in a non-standard way. Once calibrated, mainly on countries exhibiting medium relative prices values, the model reproduces the main stylized facts outlined in the literature and suggests a strategy that could make aid work.
Keywords: O11; O23; O41; F35; E62; 330; Foreign aid; Economic development; Economic growth; Quantitative approach